Uloga Paddyja Ashdowna kao visokog predstavnika u Bosni i Hercegovini / The Role of Paddy Aschdown as High Representative in Bosnia and Herzegovina - Beširović, Berina (Pregled: časopis za društvena pitanja / Periodical for social issues, 2021)
Paddy Ashdown served as High Representative in Bosnia and Herzegovina for three and a half years, during which time he was the final interpreter of the Constitution of Bosnia and Herzegovina, as mandated by the powers given in Annex 10 (High Representative) of the Dayton Peace Agreement. The function of the High Representative under Annex 10 is to integrate Bosnia and Herzegovina with the aim of achieving the best possible functioning of the state authorities and the democracy of the system. The powers of Paddy Ashdown were broader than those of the first High Representative. The so-called “The Bonn powers”, officially endorsed by the Constitutional Court's endorsement since 2000, have allowed Ashdown to make decisions with final force that can only be overturned with a new decision by himself. That Paddy Ashdown made the most of his High Representatives and did the most for the integration of B&H is substantiated by the fact that during his term, he made 430 decisions, the most significant being: dismissal of officials who obstructed the Dayton Peace Accords, police reform, tax reform, genocide acknowledgment, etc.